Bacillus encimensis sp nov isolated from marine sediment - Dastager, Syed Gulam; Mawlankar, Rahul R.; Mual, Poonam; Verma, Ashish; Krishnamurthi, Srinivasan; Joseph, Neeta; Shouche, Yogesh S. (International Journal of Systematic and Evolutionary Microbiology, 2015)
A Gram-stain-positive, rod-shaped, endospore-forming, aerobic bacterium designated SGD-V-25(T) was isolated from Veraval sediment sample, India. Strain SGD-V-25(T) was capable of growing at 25-50 degrees C (optimum 37 degrees C), pH 6-12 (optimum pH 7.0) and with 0-5 % (w/v) NaCl. The taxonomic position of this strain was deduced using a polyphasic approach and the 16S rRNA gene sequence analysis showed that the isolate belongs to the phylum Firmicutes, forming the cluster with Bacillus badius MTCC 1548(T), with which it shares highest similarity of 99.1 % with 13 nt differences. Other type strains of the genus Bacillus showed less than 96% similarity. The cell wall contained meso-diaminopimelic acid as the diagnostic diamino acid. The polar lipid profile of strain SGD-V-25(T) showed the presence of diphosphatidylglycerol, phosphatidylglycerol, phsophoglycolipid and two aminophospholipids. The predominant isoprenoid quinone was MK-7. The major cellular fatty acids were iso-C-15:0, anteiso-C-15:0, anteiso-C-17:0 iso-C-16:0, C-16:1 omega 11c and C-16:0. The genomic DNA G + C content of strain SGD-V-25(T) was 37.6 molok. On the basis of phenotypic characteristics, phylogenetic analysis and DNA-DNA hybridization, strain SGD-V-25(T) could be clearly distinguished from closely related members of the genus Bacillus, and the name Bacillus encimensis sp. nov., is proposed to accommodate this strain. The type strain is SGD-V-25(T) (= NCIM 5513(T)=DSM 28241(T)).

Bacillus cellulasensis sp nov., isolated from marine sediment - Mawlankar, Rahul R.; Thorat, Meghana N.; Krishnamurthi, Srinivasan; Dastager, Syed Gulam (Archives of Microbiology, 2016)
A novel bacterial strain NIO-1130(T) was isolated from sediment sample taken from Chorao Island, Goa Province, India, and subjected to a taxonomic investigation. The strain was Gram-positive, aerobic, and motile. Phylogenetic analysis based on 16S rRNA gene sequences placed the isolate within the genus Bacillus and strain NIO-1130(T) showed highest sequence similarity with Bacillus halosaccharovorans DSM 25387(T) (98.4 %) and Bacillus niabensis CIP 109816(T) (98.1 %), whereas other Bacillus species showed < 97.0 % similarity. Tree based on gyrB gene sequence revealed that strain bacillus group. The major menaquinone was MK-7 and the predominant cellular fatty acids were iso-C-15:0, anteiso-C-15:0, iso-C-17:0, and anteiso-C-17:0. The strain showed a DNA G+C content of 39.9 mol%. DNA-DNA hybridization studies revealed that strain NIO-1130(T) exhibits 70 % similarity with Bacillus halosaccharovorans DSM 25387(T) and Bacillus niabensis CIP 109816T. On the basis of physiological, biochemical, chemotaxonomic and phylogenetic analyses, we consider the isolate to represent a novel species of the genus Bacillus, for which the name Bacillus cellulasensis sp. nov., is proposed. The type strain is NIO-1130(T) (=NCIM 5461(T) = CCTCC AB 2011126(T)).
Keywords: Bacillus sp; Cellulase; Marine sediment; Polyphasic taxonomy